Modeling, simulation and experimental verification of hydraulic servo system - Anis Syarliza, Ahmad (2013)
The aim of this project is to model, simulate and analyze the performance of the hydraulic servo system using MATLAB and Simulink. Experiments were conducted using open loop and closed loop control. In open loop control, the experiment was conducted for various speeds by supplying voltage to actuator from 5V to 10V. The open loop experimental data were used to determine the transfer function of the system. In closed loop control, the PI, PD and PID controllers were implemented in the hydraulic servo system and the desired positions were set to 30 mm, 50 mm and 70 mm. The results of the closed loop control showed that the PID controller produced better performance. The results also indicate that the transfer function model represented the actual system very well.